The potential for aclidinium bromide, a new anticholinergic, in the management of chronic obstructive pulmonary disease - François Maltais; Julie Milot (Therapeutic Advances in Respiratory Disease, 2012)
Long-acting muscarinic antagonists (LAMAs) play a central role in the management of chronic obstructive pulmonary disease (COPD). Previously, only one LAMA (tiotropium) was available for the treatment of COPD, necessitating the development of other therapeutic options due to the heterogeneity of COPD and patient responses to treatment. This article reviews the COPD management potential of aclidinium bromide, a LAMA administered twice daily (BID) by a multidose dry powder inhaler that is indicated for maintenance treatment of COPD. Aclidinium possesses kinetic selectivity for the M 3 versus M 2 receptor and is rapidly hydrolyzed in plasma to two major inactive metabolites, resulting in a low and transient systemic exposure and minimizing the potential for systemic side effects. A pharmacokinetic study with multiple doses of twice-daily aclidinium demonstrated the short half-life of aclidinium in plasma, suggesting that a steady state may be reached as early as the second day postdose. In a phase II study, twice-daily aclidinium 400 µg provided 24-hour bronchodilation, with significant improvements versus tiotropium during the second half of the day. In two phase III studies (ACCORD I and ATTAIN), both aclidinium 200 µg and 400 µg BID provided statistically significant improvements in trough forced expiratory volume in 1 second (FEV 1 ) and other related lung function measurements. Improvements in peak FEV 1 on day 1 were comparable to those at study end, demonstrating that aclidinium provides maximal bronchodilation after the first dose that is maintained over time. Health status was significantly improved and dyspnea, nighttime and morning symptoms of COPD were likewise significantly reduced with aclidinium. Numerically greater improvements in efficacy were observed with the 400 µg dose compared with the lower dose, with similar safety profiles between the two doses and a low incidence of anticholinergic side effects. The approved therapeutic dose of aclidinium 400 µg BID is thus an effective new treatment option for patients with COPD.